Integrating Critical Thinking into Extension Programming #5: Using Critical Thinking Styles to Enhance Team Work - Alexa J. Lamm (EDIS, 2016)
The final part of the Integrating Critical Thinking into Extension Programming series, this article continues the discussion of how to take into account critical thinking methods and styles when developing Extension programs. Well-formed working groups allow members to work successfully and solve problems as a group. This 3-page fact sheet explains the importance of critical thinking styles when it comes to team work. Written by Alexa J. Lamm and published by the Department of Agricultural Education and Communication, April 2016.